2015
DOI: 10.1177/2040206616656263
|View full text |Cite
|
Sign up to set email alerts
|

Combination activity of neuraminidase inhibitor oseltamivir and α-tocopherol in influenza virus A (H3N2) infection in mice

Abstract: Evidently, α-tocopherol could be considered as prospective component of influenza therapy in combination with oseltamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Moreover, in addition to its membrane protective effect in the influenza virus target area, vitamin E manifests pronounced activities as an antioxidant agent and as a protein kinase C inhibitor and a protector of lung tissue during inflammatory lung illnesses [59,80]. The study discussed above [76] convincingly demonstrates a strong beneficial effect of the combination of vitamin E and oseltamivir in the treatment of experimental infection with influenza virus A/H3N2 in mice.…”
Section: Vitamin E In the Influenza Therapymentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, in addition to its membrane protective effect in the influenza virus target area, vitamin E manifests pronounced activities as an antioxidant agent and as a protein kinase C inhibitor and a protector of lung tissue during inflammatory lung illnesses [59,80]. The study discussed above [76] convincingly demonstrates a strong beneficial effect of the combination of vitamin E and oseltamivir in the treatment of experimental infection with influenza virus A/H3N2 in mice.…”
Section: Vitamin E In the Influenza Therapymentioning
confidence: 85%
“…The in vivo antiviral activity of the combination vitamin E + oseltamivir, expressed by a marked protective effect on the survival of influenza A virus-infected animals, was recorded when vitamin E was administered simultaneously with oseltamivir phosphate via a 5-day course post virus inoculation [76]. This effect was not observed when the vitamin E course started 120 or 48 hours before viral inoculation.…”
Section: Vitamin E In the Influenza Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the antiviral strategies make use of anti-oxidants, alpha-tocopherol (Figure 19) enjoys a long history since 1960s (263)(264)(265)(266). Further researches revealed that alpha-tocopherol (or combination) could normalize the lipid peroxidation processes caused by viral infection (264,(267)(268)(269)(270)(271)(272).…”
Section: Anti-oxidantsmentioning
confidence: 99%
“…A classical combination is M2 blockers and NA inhibitors to avoid drug-resistance. Many studies have been carried out to evaluate the efficacy of combination therapies and single-drug treatment, and most combination therapies showed superior outcomes in mice models (272,(318)(319)(320)(321).…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%